Paralic foraminiferal record of seven large Holocene earthquakes in eastern New Zealand - Hayward, Bruce W.; Grenfell, Hugh R.; Sabaa, Ashwaq T.; Carter, Rowan; Morley, Margaret S.; Cochran, Ursula; Lipps, Jere H. (Anuário do Instituto de Geociências, 2006)
Abstract